Ustadz Hanan Attaki's Da'wah Style Using Social Media as a Figure That Inspires Gen-M - Nunik (Kawakib: Journal of Multidisciplinary Research, 2024)
In the development of this digital era, a lot of electronic media has spread widely. Currently, social media networks are very influential in all levels of society, including children and parents who now use gadgets in their daily lives. In this digital era, there are so many good and bad shows like two blades. Children need parental supervision when using gadgets. Let's compare it with when we were children, when children were growing up, they were supposed to play outside with their peers and use simple tools. but now they prefer to just lie down and do finger exercises. Therefore, parental supervision is needed. For example, giving children a schedule for using gadgets, setting settings on children's gadgets for 6-7 hours of use. In today's developments, all levels of society can absorb anything from these social networks, from videos, photos, editing, video games, etc. Private TV is no longer popular, broadcasts on television are no longer good for children (not child-friendly), there are only political issues if not just love issues. The TV at home nowadays is just a display. Everyone can become famous thanks to this social media. Nowadays, you don't need to be an artist if you want to be famous through one of the applications, for example TikTok, you can already be famous if you have a lot of followers.